Video Program Hotroom Pada Bagian Lighting Informasi Pada Metro TV - Erna Astriyani; Muhammad Khaidir Fahram; Achmad Adam Pebrianto (UNIVERSITAS RAHARJA, 2020)
Video Program Hotroom is a concept of this Program is legal consultation. For people who have unresolved Legal cases can complain. Or consult the Program. Some examples can be used as a measure, such as the strong demands of civil society that hopes fulfillment in the form of a number of accommodations or a decent living needs, the research methods used in this study Including Data collection, Media planning analysis, and Media production concept (KPM) which includes: Pre production, production, and post production. Through the media information Video Program Hotroom is designed to be informed through: Metro TV Target that the Video program is expected Hotroom namely, the community can know the problems faced by the community, and can increase the number of Viewers who saw the Hotroom Program show.